Mediating role of trust between emotional intelligence and positive functioning of personality - Kryazh, I; Grankina-Sazonova, N (Fundamental and Applied Researches in Practice of Leading Scientific Schools, 2018)
This paper presents the theoretical justification and empirical confirmation of the hypothesis that trust mediates the relationship between emotional intelligence and positive personality functioning. The positive functioning is regarded as association of psychological wellbeing and hardiness. The research was held on the sample of 213 students of different specialties. Data processing included correlation analysis, hierarchical regression analysis, and structural equation modeling (SEM). By the results of regression analysis, general trust and self-trust are significant and rather strong predictors of positive functioning. According to our hypothesis there were developed structural models describing the interrelations between indexes of EI, trust and positive functioning. The models with trust as mediator between EI and positive functioning showed good accordance to the outgoing data. We also received confirmation of the assumption that psychological wellbeing and hardiness may be associated in the framework of the positive functioning construct. Wherein trust performs as a separate phenomenon, one of the important conditions of positive functioning, in refraction through which the “positive potential” of personality`s dispositions and abilities may be realized. Besides, we received empirical confirmation of theoretical grounding for association of hardiness and psychological wellbeing in a framework of positive functioning construct.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology::Applied psychology; wellbeing; trust; hardiness; emotional intelligence; positive functioning of a personality